Does Ibuprofen Increase Bleed Risk for Pediatric Tonsillectomy?. (July 2021) - Leung, Peggy; DeVore, Elliana Kirsh; Kawai, Kosuke; Yuen, Sonia; Kenna, Margaret; Irace, Alexandria L.; Roberson, David; Adil, Eelam
Objective: To evaluate risk factors for pediatric posttonsillectomy hemorrhage (PTH) and the need for transfusion using a national database. Study Design: Retrospective cohort study. Setting: The study was conducted using the Pediatric Health Information System (PHIS) database. Methods: Children ≤18 years who underwent tonsillectomy with or without adenoidectomy (T±A) between 2004 and 2015 were included. We evaluated the risk of PTH requiring cauterization according to patient demographics, comorbidities, indication for surgery, medications, year of surgery, and geographic region. Results: Of the 551, 137 PHIS patients who underwent T±A, 8735 patients (1.58%) experienced a PTH. The risk of PTH increased from 1.33% (95% confidence interval [CI]: 1.15%, 1.53%) in 2010 to 1.91% (95% CI: 1.64%, 2.24%) in 2015 ( P < .001). Older age (≥12 vs <5 years old: adjusted odds ratio [aOR] 3.17; 95% CI: 2.86, 3.52), male sex (aOR 1.11; 95% CI: 1.05, 1.17), medical comorbidities (aOR 1.18; 95% CI: 1.08, 1.29), recurrent tonsillitis (aOR 1.15; 95% CI: 1.07, 1.24), and intensive care unit admission (aOR 1.74; 95% CI: 1.55, 1.95) were significantly associated with an increased risk of PTH. Use of ibuprofen (aOR 1.36; 95% CI: 1.22, 1.52), ketorolac (aOR 1.39; 95% CI: 1.14, 1.69), anticonvulsant (aOR 1.23; 95% CI: 1.03, 1.76), and antidepressants (aOR 1.35; 95% CI: 1.03, 1.76) were also associated with an increased risk of PTH. The need for blood transfusion was 2.1% (181/8735). Conclusion: The incidence of PTH increased significantly between 2011 and 2015, and ibuprofen appears to be one contributing factor. Given the benefits of ibuprofen, it is unclear whether this increased risk warrants a change in practice.